Représentations de l'environnement et de l'agir dans l'environnement chez des élèves du primaire des Îles-de-la-Madeleine, Québec, Canada - Pauline Côté; Mireille Picard (VertigO)
Islands are many-faceted milieus whose specific features make them relevant cases for studying environmental education processes. Such processes can rely on islanders place attachment and strong sense of identity. Our research took place among primary school children. We explored their representations of the environment as well as their willingness to act on the environment. Our study of social representations of the environment led us to the elaboration of a model of educational intervention that would meet the specificities of the insular population.